Communicating the probabilistic seasonal forecast for a better farming management and decisions at Kaffrine, Senegal - Ndiaye, Ousmane (CGIAR Research Program on Climate Change, Agriculture and Food Security, 2011)
This is a combined report on the workshop interaction with framers on probabilistic seasonal forecasting on June 4th and 5th, and the follow up workshop on communicating the actual seasonal forecasting on June the 8th, 2011 both held in Kaffrine (Senegal). The first workshop was designed to expose farmers on probabilistic seasonal forecasting and also to establish dialogue and trust between farmer’s organizations and experts working on climate forecasting and farming in general. Emphasis was made to listen the framers first and better understand their decision system. This is a first step toward helping small-scale farmers to make appropriate management decisions for improved agricultural based on probabilistic seasonal climate forecast. The second workshop was to deliver the actual seasonal forecast and to ensure they can interpret it. We also distributed some rain gauges and offer training on their installation and use. We chose the site of Kaffrine in Senegal for many reasons. Kaffrine is located in the midst of the transition zone from the Sahelian towards the Sudan Savannah zone with annual rainfall averages of around 500 mm in the northern, 600 mm at Kaffrine, and around 800 mm in the southwestern part of the area. Dominant soils are deep sandy (“Dior”). Predominant cropping systems are based on pearl millet, peanut and cowpea, all generally not intensified and cropped without agricultural input. In the south, peanut is intensified using inputs, and maize, sorghum, lowland rice and sesame are also cropped. Main constraints to agricultural production are high rainfall variability, poor soil fertility, no attractive markets and high poverty levels with low access to capital.